Equilibrium constants and protonation site for N-methylbenzenesulfonamides - Moreira, José A.; Rosa da Costa, Ana M.; García-Río, Luis; Pessêgo, Márcia (Beilstein Journal of Organic Chemistry, 2011)
The protonation equilibria of four substituted N-methylbenzenesulfonamides, X-MBS: X = 4-MeO (3a), 4-Me (3b), 4-Cl (3c) and 4-NO2 (3d), in aqueous sulfuric acid were studied at 25 °C by UV–vis spectroscopy. As expected, the values for the acidity constants are highly dependent on the electron-donor character of the substituent (the pKBH+ values are −3.5 ± 0.2, −4.2 ± 0.2, −5.2 ± 0.3 and −6.0 ± 0.3 for 3a, 3b, 3c and 3d, respectively). The solvation parameter m* is always higher than 0.5 and points to a decrease in the importance of solvation on the cation stabilization as the electron-donor character of the substituent increases. Hammett plots of the equilibrium constants showed a better correlation with the σ+ substituent parameter than with σ, which indicates that the initial protonation site is the oxygen atom of the sulfonyl group.
Keywords: linear free-energy relationships; N-methylbenzenesulfonamides; protonation equilibrium